2010
DOI: 10.2478/v10045-010-0055-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glomus Mosseae (Arbuscular Mycorrhizal Fungus) On Host - Parasite Relationship of Meloidogyne Incognita (Southern Root-Knot Nematode) on Four Improved Cowpea Varieties

Abstract: Abstract:Two pot experiments and a field study were conducted in a Randomized Complete Block Design (RCBD). The experiments were conducted to determine the effect of Glomus mosseae, a mycorrhiza fungus, on the reaction of four improved cowpea varieties to Meloidogyne incognita. Cowpea plants were inoculated with a single or a combination of 5 000 eggs of M. incognita and 50 g of G. mosseae inoculum containing 5 spores/g of soil. The standardized method of screening and reporting resistance of crop germplasm to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The earlier findings of effectiveness of AM fungus, G.mosseae in reducing R. reniformis population and increasing plant growth and yield of cotton also support the present findings (Seenivasan and Devrajan, 2008). In support of the present study, Odeyemi et al (2010) also reported that inoculation of G. mosseae @ 50g (5 spores/g of soil) reduced reproduction factor of M. incognita on four improved cowpea varieties.…”
Section: Resultssupporting
confidence: 89%
“…The earlier findings of effectiveness of AM fungus, G.mosseae in reducing R. reniformis population and increasing plant growth and yield of cotton also support the present findings (Seenivasan and Devrajan, 2008). In support of the present study, Odeyemi et al (2010) also reported that inoculation of G. mosseae @ 50g (5 spores/g of soil) reduced reproduction factor of M. incognita on four improved cowpea varieties.…”
Section: Resultssupporting
confidence: 89%
“…This fungus parasitizes the egg of root-knot nematode and its other life stages. Similarly, many researchers have reported the effectiveness of arbuscular mycorrhizal fungi (AMF) in the control of root-knot nematodes and other nematodes in many crops (Diederichs 1987;Shreenivasa et al 2007;Zhang et al 2008;Odeyemi et al 2010). The mechanism involved in nematode suppression by AMF is still topical (Gera Hol and Cook 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This is indicative that the G. mosseae improves nutrient supply along with the nematicidal properties exhibited by C. odorata powder. Reduction in M. incognita population in this study could have been as result of mycorrhizal infection in the roots of maize which had earlier been confirmed to improve phosphorus nutrition and that they are obligate feeders competing for space in the aburscules of maize root alongside M. incognita (Odeyemi et al 2010). It is evident that an increased capacity for nutrient acquisition resulting from mycorrhiza association could help the plant resulting in stronger plant health.…”
Section: Archives Of Phytopathology and Plant Protection 1595mentioning
confidence: 52%